The formation of some skills throuot teaching tasks in combinatorial themes (Original) (Revista científica Olimpia, 2021)
This research work accomplished for the sake of favoring the formation of teaching skills of combinatorial themes of chess, in the Physical Culture carreer at Holguín University, as from the insufficiencies detected in the process of teaching learning process of this contents itself. Methodological established for teaching contribute teaching tasks designed in accord with the steps themselves. The obtained results evidence the functionality of the teaching implemented tasks.